INTERFERENCE OF THE NUMBER OF REMOTE CONTROL VALVES IN USE ON THE ENERGY PERFORMANCE OF AN AGRICULTURAL TRACTOR WITH PRODUCTIVITY MANAGEMENT - Neto,Lauro S. (2020)
ABSTRACT The hydraulic remote control system allows the transfer of energy from the engine through a flow of hydraulic oil to engines and implements pulled by agricultural tractors, which can interfere with its energy and operational performance. This study aimed to evaluate the interference of the number of remote control valves in use on the operational and energy performance of an agricultural tractor, using a productivity management system. The experiment was conducted in a strip-plot design, with five replications and three treatments, which consisted of the number of remote control valves in use (1, 2, or 3), totaling 15 experimental units. The results were subjected to normality and homogeneity tests and analysis of variance, followed by the Tukey test when it was significant. The highest number of valves in use interfered with the operational speed, power and efficiency on the drawbar, specific fuel consumption, and engine thermal efficiency, thus reducing the energy and operational performance of the agricultural tractor.